Early first‐line treatment response and subsequent disability worsening in relapsing–remitting multiple sclerosis. (26th December 2021) - Koch, Marcus W.; Mostert, Jop; Repovic, Pavle; Bowen, James D.; Wolinsky, Jerry S.; Lublin, Fred D.; Strijbis, Eva; Cutter, Gary
Abstract: Background and purpose: Treatment success in relapsing–remitting multiple sclerosis (RRMS) is generally determined using relapse frequency and magnetic resonance imaging (MRI) activity in the first 6 or 12 months on treatment. The association of these definitions of short‐term treatment success with disability worsening and disease activity in the longer term is unclear. In this study, we investigated risk factors associated with early first‐line treatment failure in RRMS, and the association of early treatment failure with subsequent disability worsening or "no evidence of disease activity" (NEDA‐3) status. Methods: We used data from CombiRx (clinicaltrials.gov identifier NCT00211887) to investigate risk factors associated with early treatment failure, and the association of early treatment failure at 6 and 12 months with subsequent disability worsening or NEDA‐3 at 36 months. Results: CombiRx included 1008 treatment‐naïve participants with RRMS, who were randomly assigned to treatment with glatiramer acetate, interferon beta, or the combination of both. Early treatment failure at 6 or 12 months by several definitions was associated with NEDA‐3 failure at 36 months, but not with subsequent disability worsening at 36 months. Expanded Disability Status Scale (EDSS) was the only baseline characteristic associated with the risk of disability worsening at 36 months. Approximately 70% of NEDA‐3 failures occurred due to MRI activity, and <10% occurred due to EDSS worsening. Conclusions: Our investigation shows that current definitions of early treatment failure in RRMS are unrelated to patient‐relevant disability worsening at 36 months of follow‐up. Further research into useful definitions of treatment success and failure in RRMS is needed. Abstract : Relapses and magnetic resonance imaging (MRI) activity in the first 6 or 12 months on treatment are usually used to determine treatment success in relapsing–remitting multiple sclerosis. An investigation using a large trial dataset shows that current definitions of early treatment success are unrelated to patient‐relevant disability worsening at 36 months of follow‐up. Failure to achieve "no evidence of disease activity" (NEDA‐3) occured due to MRI activity in approximately 70% of cases, and due to Expanded Disability Status Scale worsening in less than 10% of cases.